DESCRIPTION OF FACTORS AFFECTING MEDICAL RECORD FILLING AT THE DENTAL CLINIC IN SEMARANG - Sugiarto, Febia Astiawati; Wardhana, Erdianto Setya; Arbianti, Kusuma; Darmawan, Nabila Alifia (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: A clinic a health service place that provides health services. Based on Peraturan Menteri Kesehatan RI No. 9 tahun 2014, every clinic has an commitment to conduct therapeutic records. Restorative Records could be a record that contains records and reports that contain the personality of the persistent, the comes about of the examination, treatment that has been given, as well as other activities and administrations provided by the doctor to the patient. This study aimed is to look at the description of the factors that affecting medical record filling at the dental clinic in Semarang.Method: This study used a descriptive observational research type of quantitative approach with cross-sectional inquire about plan. Information gotten from questionnaires will be assessed percentage. The research will be processed using SPSS so that it will produce data on the frequency of each factor and the frequency of each question.Result: The results showed that judging from the knowledge factor showed good and less results, motivation and medical record form material showed good results, while the reward method showed good and sufficient results. Conclusion: there were factors that showed results in the category was sufficient, less, and good against filling medical records in the dental clinic of Semarang City.